2019
DOI: 10.3892/etm.2019.7184
|View full text |Cite
|
Sign up to set email alerts
|

VEGF and sFLT-1 in serum of PIH patients and effects on the foetus

Abstract: The expression of vascular endothelial growth factor (VEGF) and soluble fms-like tyrosine kinase-1 (sFLT-1) in the serum of patients with pregnancy induced hypertension (PIH) syndrome and its effects on the foetus was explored. A total of 105 cases of PIH pregnant women admitted to The First People's Hospital of Changzhou from March 2015 to February 2018 were divided into 3 groups according to the severity of the patients condition. Group A (n=35) was hypertension complicating pregnancy, group B (n=46) was mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…After uterine and placental perfusion causes oxidative stress in vivo and hypoxia, sFlt‐1 prevents the binding of endothelin receptors to PlGF or VEGF on the cell surface, chelates free PlGF and VEGF and induces endothelial cell dysfunction. These processes lead to maternal hypertension and vasoconstriction 32 . Therefore, we speculate that the level of VEGF decreases when the level of sFlt‐1 increases and that sFlt‐1 affects the infiltration of trophoblast cells by inhibiting their synthesis, thus resulting in pre‐eclampsia.…”
Section: Discussionmentioning
confidence: 95%
“…After uterine and placental perfusion causes oxidative stress in vivo and hypoxia, sFlt‐1 prevents the binding of endothelin receptors to PlGF or VEGF on the cell surface, chelates free PlGF and VEGF and induces endothelial cell dysfunction. These processes lead to maternal hypertension and vasoconstriction 32 . Therefore, we speculate that the level of VEGF decreases when the level of sFlt‐1 increases and that sFlt‐1 affects the infiltration of trophoblast cells by inhibiting their synthesis, thus resulting in pre‐eclampsia.…”
Section: Discussionmentioning
confidence: 95%
“…Some TTTS cases may present with hypoxia or ischemia in the donor villi, which lead to the hypoxia/ischemia in donor villi due to the decreased fetal villi perfusion rather than the abnormality of placenta circulation 25 . The expression of VEGF-R1 has been reported to be inversely correlated with fetal weight at birth and Apgar score in patients with gestational hypertension 26 . Our results showed a significant decrease in VEGF-R1 and VEGF-R2 levels in twin pregnant women with TTTS after being treated with laser surgery suggesting a role of VEGF-R1 and VEGF-R2 in assessing the effectiveness of TTTS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10] By Tang et al, on 105 PE subjects, a study was piloted, they found a sound increase in sFlt1 levels in PE and complicated PE pregnancies, especially in intrauterine fetal growth and development. [11] In a cohort study, in California on 97 pregnant women tested sFlt1 levels by comparing nulliparous and multiparous women, in first and second pregnancies and observed an increase in their sFlt1 levels during first pregnancies than second pregnancy and can be a predictor marker in primigravida. As it is a known factor that primigravida women were at risk for PE.…”
Section: Discussionmentioning
confidence: 99%